Zero Divisor Graph Of ZpM qr with Applications - Nazar Shuker; Husam Mohammad; Luma Khaleel (Al-Rafidain Journal of Computer Sciences and Mathematics, 2020)
In this paper, we study zero-divisor graph of the ring Zpmqr and give some properties of this graph. Also, we find the chromatic number, Hosoya polynomial and Wiener index of this graph.